2015
DOI: 10.1177/1479164115610247
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of macro- and microvascular complications in patients with type 2 diabetes and kidney disease with or without albuminuria in a single Chinese Diabetes Centre

Abstract: The prevalence of diabetic retinopathy was graded according to the estimated glomerular filtration rate declining in albuminuric patients while the prevalence of low ankle-brachial index was gradually increased in normoalbuminuric patients, indicating the diverse underlying mechanisms of mild to moderate chronic kidney disease between these two phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
1
7
0
1
Order By: Relevance
“…Few reports described the clinical characteristics of normoalbuminuric DKD with vascular complications. A previous report compared these characteristics with the characteristics of patients with micro-/macroalbuminuria [15]. Tingjun Wang et al [24] also reported that low-grade albuminuria is related to LV hypertrophy and diastolic dysfunction in patients with hypertension; we also find similar relation, but it did not show the joint relationship between albuminuria and eGFR.…”
Section: Features Of Normoalbuminuria With Vascular Complicationssupporting
confidence: 43%
See 2 more Smart Citations
“…Few reports described the clinical characteristics of normoalbuminuric DKD with vascular complications. A previous report compared these characteristics with the characteristics of patients with micro-/macroalbuminuria [15]. Tingjun Wang et al [24] also reported that low-grade albuminuria is related to LV hypertrophy and diastolic dysfunction in patients with hypertension; we also find similar relation, but it did not show the joint relationship between albuminuria and eGFR.…”
Section: Features Of Normoalbuminuria With Vascular Complicationssupporting
confidence: 43%
“…Hence, the joint relationship of albuminuria and eGFR with vascular diseases has not been elaborated, and different conclusions have been obtained [13,14]. Wu et al [15] investigated the relationship between DR, neuropathy, and low ankle-brachial index (ABI) in patients with T2D ac-companied by mild to moderate CKD. They found that the prevalence of diabetic retinopathy (DR) was graded according to the decline in the eGFR in patients with albuminuria, while the prevalence of peripheral arterial disease (PAD) gradually increased in patients with normoalbuminuria [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal complications such as clinical nephropathy and chronic kidney disease (CKD) also contribute to the clinical burden in patients with T2D. These complications are affected by disease duration and patient age, with prevalence reported between 1%-25% in EMG [115,116], and 5%-20% in EST markets [116,117]. Variations in those numbers have been observed, mostly due to differences in diagnostic practices as well as diseases durations.…”
Section: Epidemiology: Complicationsmentioning
confidence: 99%
“…Due to heterogeneity in patient populations and diagnostic practices, no clear trends were observed between EMG and EST markets with respect to CKD or nephropathy epidemiology. Prevalence of nephropathy is known to be influenced by the other co-morbidities such as obesity and hypertension [116,117], the latter being a common and major contributing factor to the development of renal disease in T2D patients [119,120]. Crosssectional studies from EST and EMG markets which look into the characteristics of CKD patients show similarities in terms of severity distribution, with 60-90% of CKD patients being classed as stage 1 or 2 [121,122].…”
Section: Epidemiology: Complicationsmentioning
confidence: 99%